Utilização da RMN aliada a métodos quimiométricos na análise de méis e aguardentes - Boffo, Elisangela Fabiana (2009)
Apiculture has been increasing a lot in the last years in Brazil, which already is one of the greatest exporters of honey. Productive chain of aguardentes has also risen, and both products are considerably important in Brazilian agribusiness. Therefore, the quality control of these products is essential. The present work describes the use of SNIF-NMR technique and chemometric methods applied to 1H NMR data aiming to evaluate chemical differences that are related to samples authenticity. Using SNIFNMR technique, it was observed that the isotopic ratio of the methyl group from ethanol (2H/1H)I is related to the biosynthetic origin of carbohydrates produced by plants (C3, C4 and CAM mechanisms used to CO2 fixation). In honeys analysis, was observed a good discrimination between those produced by C3 plants (eucalyptus, citrus, assa-peixe, Jataí and wildflowers) and those from C4 plants (sugarcane). C3 plants showed (2H/1H)I values near 100 ppm (parts per million) and from C4 plants showed higher values, in approximately 12 ppm. Some commercial samples presented (2H/1H)I values near those determined for sugarcane honeys. In aguardentes analysis, a discrimination of approximately 12 ppm between those from C3 (grape, banana and cassava) and C4 (sugarcane and maize) plants was also observed. Aguardentes from CAM plants (pineapple) showed intermediate values. (2H/1H)I data of honey aguardentes were similar to those of C3 plants. For banana, peach, coconut and pineapple commercial samples (from C3 plants), (2H/1H)I values were similar to those of sugarcane aguardentes. Chemometrics applied to 1H NMR spectra data allowed the discrimination among honeys from eucalyptus, citrus and wildflowers, which were produced in São Paulo state. Moreover, honeys, which showed anomalous behaviour, were discriminated due to citric acid and HMF presence. KNN, SIMCA and PLS-DA methods were suitable for classification of commercial honeys from this state. Honeys from different Brazilian regions could not be discriminated since they showed very similar characteristics. However, adulterated and different types of honeys were discriminated. PCA and HCA analyses applied to 1H NMR spectra of aguardentes allowed to discriminate the different types of such samples. Sugarcane with lemon aguardentes and cassava aguardentes were distinguished. Adulterated aguardentes from banana, peach, coconut and pineapple showed 1H NMR spectra quite similar, what suggested that they were made from the same raw material.